Analisis Diskriminasi Sosial Dalam Novel “Ayah Mengapa Aku Berbeda” Karya Agnes Danovar (Tinjauan Sosial Dan Moral) - Ayu Indari Tania Napitupulu; Alfitriana Purba (LPPM STIKes SITI HAJAR dan Insight Power, 2022)
Novel Ayah Mengapa Aku Berbeda? Agnes Davonar's works include a good form of literary work and are interesting to read. The researcher's interest in this novel is caused by the act of social discrimination against a child. The characters in this novel give an example to the children out there that the act of social discrimination does not need to happen again, both in the school environment and the surrounding environment. Even though the character is born with a disability, he has a very strong will to achieve a goal. The research problem is about what are the types of internal social discrimination and the factors that cause discrimination in the novel Ayah Mengapa Aku Berbeda? by Agnes Davonar. The purpose of this study is to find out what types of social discrimination are and the factors that cause discrimination in the novel Ayah Mengapa Aku Berbeda? by Agnes Davonar. The research design in writing this proposal is a qualitative descriptive study using the text study method. The object studied is in the form of a literary text, namely the novel Ayah Mengapa Aku Berbeda by Agnes Davonar. The results of his research are forms of social discrimination in the novel Ayah Mengapa Aku Berbeda? Agnes Davonar's work is basically discrimination against people with disabilities. Due to having a disability as a disability, the little girl named Angel often gets unfair treatment from her peers. The treatment that Angel gets because of his physical limitations causes him to be the subject of insults, insults and also ridicule from his friends at school. The suggestion in this novel is that the reader learns to look at the positive side of every shortcoming. And invites readers to realize that everything that happens in this life is God's plan.Keywords: Literature, Qualitative, Discrimination, Diffable